2013
DOI: 10.1016/j.cub.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

M1 Corticospinal Mirror Neurons and Their Role in Movement Suppression during Action Observation

Abstract: SummaryEvidence is accumulating that neurons in primary motor cortex (M1) respond during action observation [1, 2], a property first shown for mirror neurons in monkey premotor cortex [3]. We now show for the first time that the discharge of a major class of M1 output neuron, the pyramidal tract neuron (PTN), is modulated during observation of precision grip by a human experimenter. We recorded 132 PTNs in the hand area of two adult macaques, of which 65 (49%) showed mirror-like activity. Many (38 of 65) incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
197
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(227 citation statements)
references
References 39 publications
21
197
1
1
Order By: Relevance
“…In non-human primates, activity of mirror neurons have been found in different regions of the motor system (Lemon, 2010), and mirror neurons have been identified in the ventral premotor cortex (see review by Kilner and Lemon, 2013), primary motor cortex (Vigneswaran et al , 2013), inferior parietal lobule (Casile, 2013), and ventral and lateral intraparietal areas. In contrast the existence of a MNS in humans, has been surmised almost entirely by functional MRI (fMRI) and Mu rhythm in the EEG a measure of a resting motor state, which is normally suppressed by input from an action observation or movement execution.…”
Section: Cerebral Localisationmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-human primates, activity of mirror neurons have been found in different regions of the motor system (Lemon, 2010), and mirror neurons have been identified in the ventral premotor cortex (see review by Kilner and Lemon, 2013), primary motor cortex (Vigneswaran et al , 2013), inferior parietal lobule (Casile, 2013), and ventral and lateral intraparietal areas. In contrast the existence of a MNS in humans, has been surmised almost entirely by functional MRI (fMRI) and Mu rhythm in the EEG a measure of a resting motor state, which is normally suppressed by input from an action observation or movement execution.…”
Section: Cerebral Localisationmentioning
confidence: 99%
“…It remains to be confirmed that suppression mirror neurons are present in humans (Mukamel et al, 2010), but there are daily occasions when one wants to covertly imitate an observed action, allowing the observer to watch the actor, while using their own motor system to identify and categorize the observed movement, without the activation overflowing into selfmovement (Vigneswaran et al , 2013).…”
Section: Als Hand Function and Mirror Neuronsmentioning
confidence: 99%
“…The authors suggested that this PTN suppression might be involved in the inhibition of the observer's movement during action observation. In a following study, they applied the same paradigm to PTNs recorded from primary motor cortex (F1) [36]. About half of these neurons were modulated during action observation.…”
Section: New Findings On Visual Properties Of Mirror Neurons (A) Mirrmentioning
confidence: 99%
“…Thus, unlike actual performance, the observation of the second, reversed, sequence did not interfere with the expression of the delayed gains for the initially trained sequence. The extent of overlap in brain regions engaged during actual performance and in action observation is not clear (Hari et al 1998;Strafella and Paus 2000;Buccino et al 2001;Grèzes and Decety 2001;Rizzolatti and Craighero 2004;Cross et al 2009); some brain areas, specifically, the primary motor cortex (M1) were found to be activated more intensely (Caetano et al 2007;Gazzola and Keysers 2009;Vigneswaran et al 2013) or even exclusively (Frey and Gerry 2006;Cross et al 2009) during actual practice. This is of importance because M1 is a key area for movement sequence skill memory (Karni et al 1995(Karni et al , 1998Hikosaka et al 2002;Gabitov et al 2014).…”
mentioning
confidence: 99%